Study of Agribusiness 4.0 – Technologies, challenges and benefits in Agribusiness (Research, Society and Development, 2022)
A study is presented on Agribusiness 4.0 (Agro 4.0) and its evolution over the years, and how technologies such as the Internet of Things (IoT), Big Data, Remote Sensing and Drones and Machine Learning are being applied in Agro 4.0. The benefits and challenges of technologies and state of the art in Agro 4.0 are also presented. The objective of the work is to carry out bibliographic research on Agro 4.0 and identify the main technologies adopted, as well as benefits and challenges of them. In this qualitative-quantitative review, articles, dissertations and theses were selected from the Scielo and Google Scholar databases, and books were also selected for the work. The study of the present work is justified by the growth of technologies in Agro with a focus on state-of-the artificial intelligence works in this field. In this sense, it is possible to conclude that Agro 4.0 is expanding and in a possible transition to Agro 5.0.